Study of Geomagnetic Storms Associated with Solar Wind and Interplanetary Parameters During Solar Cycles 23 and 24 - Dharmashaktu, H.; Lohani, N. K.; Tewari, M. (Journal of Scientific Research, 2024)
The aim of this paper is to investigate the relationship between solar wind parameters, such as solar wind speed (V), interplanetary magnetic field IMF (B, Bz) and geomagnetic activity index (Dst, Ap). We identified 103 intense geomagnetic storms (GMS) associated with decrease in Dst (disturbance storm time) ≤ -100nT during 1997- 2006 and 2011-2018, the period spanning over solar cycle 23 and 24. A comparative study has been done using the superposed epoch analysis, often used to demonstrate an effect or a periodicity (Chree analysis). The strength of the geomagnetic storm (Dst) shows significant dependency on the interplanetary magnetic field (IMF) B. The average correlations during solar cycles 23 and 24 are -0.60 and -0.62 respectively, which is quite reasonable. Considering previous studies, Dst is strongly dependent on the southward magnetic field component (Bz), whereas in our present study the average correlation coefficient has been found to be weak and the time lag between Bz minimum and Dst minimum has found up to 5 hours. These results indicate that significant growth in Bz occurs before the main phase of the GMS and not during the main phase. Dst shows high correlation with solar wind speed V during solar cycle 23 (-0.71) than 24 (-0.58) whereas the Ap index exhibits low average correlation with V for solar cycle 23 (+0.51) and SC 24 (+0.31). The correlation coefficient between Dst and Ap index for solar cycle 23 (−0.62) is lower than that for solar cycle 24 (-0.72). Dst shows higher anti-correlation with BV then with B alone but shows low correlation with BzV.